Simulation results of a 1 kW photovoltaic system with MPPT function in the inverter - Gonçalves, Henrique (2012)
Photovoltaic pumping systems are commonly used in remote regions, where the access to electrical energy is difficult or very expensive. This paper presents simulation results of a 1 kW photovoltaic system proposed in a cascade topology, consisting of a DC-DC boost converter followed by a single-phase inverter. The Maximum Power Point Tracking (MPPT) function is performed by the inverter, instead of by the DC-DC converter, as usually is done. The MPPT function uses an Incremental Conductance algorithm. This paper presents simulation results, in steady state and transient conditions, for the proposed photovoltaic system operating in different circumstances, which in real facilities can be caused by solar radiation variations.